Wearable graphene-based fabric electrodes for enhanced and long-term biosignal detection - Babar Ali; Hossein Cheraghi Bidsorkhi; Alessandro G. D'Aloia; Marco Laracca; Maria S. Sarto (Sensors and Actuators Reports, 2023)
Wearable health sensing devices are crucial and the development of multi-sensing textiles for non-invasive and continuous long-term biosignal monitoring is of primary interest. Nowadays, different wearable sensors are available but they usually lack comfort for continuous use during normal daily life activities. In this study, new graphene-based flexible dry electrodes are investigated to overcome the limitations of the currently available electrodes. Briefly, they are realized through casting PVDF (polyvinylidene fluoride)/GNP (graphene nanoplatelets) nanocomposite over commercial textiles. These electrodes are soft and flexible and adhere more easily to the skin. In terms of performance, the PVDF/GNP electrodes show lower impedance per unit area compared to commercial ones, hence they can be employed for biosignal detection. In particular, the developed electrodes are used for electrocardiogram (ECG) signal monitoring. The recorded ECG signal-to-noise ratio (SNR) reached up to 40 dB and all necessary ECG signal features and intervals are clearly distinguishable. Furthermore, the essential ECG signal intervals on each cadiac cycle show very small variations in time. Finally, the superhydrophobic property allows the electrodes to be used repeatedly after washing. As a final note, the developed dry PVDF/GNP electrodes provide reusability, biocompatibility, good skin-electrode contact, and no signs of skin irritation.